Occupational language requirements and the value of English in the US labor market - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2007)
This paper is concerned with the English language requirements (both level and importance) of occupations in the United States, as measured by the O*NET database. These scores are linked to microdata on employed adult (aged 25 to 64) males, both native born and foreign born, as reported in the 2000 Census, one percent sample. Working in an occupation that requires greater English language skills, whether measured by the level of these skills or the importance of English for performing the job, has a large effect on earnings among the native born, and an even larger effect among the foreign born. This effect is reduced by 50 percent, but is still large, when worker characteristics, including their own English language skills, are held constant. Earnings increase with the respondent's own proficiency in English, with the English proficiency required for the occupation, and when those with high levels of proficiency work in jobs requiring English language skills (interaction effect). There is, therefore, a strong economic incentive for the matching of worker's English skills and the occupation's requirements, and this matching does tend to occur in the labor market.
urn:nbn:de:101:1-20080415114
Keywords: 330; Beruf; Migranten; Sprache; Qualifikation; Humankapital; Lohnstruktur; USA